Bimetallic copper-cobalt oxide/graphene nano-composite: Potential as a pseudocapacitive electrode and OER-HER electrocatalyst - Sahoo K.; Kumar D.; Kushwaha V.K.; Verma V.K.; Basu S.; Indra A.; Sonawane S.H. (My University, 2025)
Over the last few decades to limit fossil fuel usage for their petrifying effect on the environment and economy, electrochemistry has been chosen as a viable option where both generation and long-term storage of clean energy is possible. Nanocomposites of graphene and transition metal oxides are currently explored as efficient electrode materials in electrochemistry where diverse energy storage and generation functionalities can be accomplished. Keeping in view multiple application potentials both in energy storage and hydrogen production, copper-cobalt oxide/graphene (CCO/GO) nanocomposite was prepared by a single-step thermochemical reduction technique assisted by ultrasonication. Prepared CCO/GO nanocomposite characterized via HR-XRD, XPS, HR-TEM, Raman, and FTIR analysis revealed Cu0.3Co2.7O4 cubic spinel type structure forming composite with graphene oxide. The nanocomposite having an overall morphology of custard apple type (∼130 nm) showed multiple functionalities both in electrochemical energy storage and electrocatalysis. From an energy storage prospect, CCO/GO nanocomposite tested to be pseudocapacitive in nature both in a 3-electrode and 2-electrode mode whose specific capacity is ∼5 times higher as compared to parent GO material. Similarly, the nanocomposite displayed excellent redox stability (∼87 % capacitance retention) over 8000 cycles of operations, and the obtained power density of 275 W/kg @ 1 A/g is high in comparison with other graphene-multimetallic oxide composites. Lower OER overpotential (η = 290 mV), HER overpotential (η = 310 mV), and chronoamperometric (CA) stability values demonstrated its superior electrocatalytic activity and established the potential of prepared nanocomposite to act as a dual-mode catalyst in water splitting process. © 2025 Elsevier Ltd